Validation of Takotsubo Syndrome Scoring System - Dana Deeb; Ranel Loutati; Louay Taha; Mohammad Karmi; Akiva Brin; Ofir Rabi; Nir Levi; Noam Fink; Pierre Sabouret; Mohammed Manassra; Abed Qadan; Motaz Amro; et al. (Diagnostics)
Background: Takotsubo syndrome (TS) mimics acute coronary syndrome in 1% to 3% of patients presenting with chest pain, ECG changes and echocardiographic transient apical wall hypokinesia. Objectives: This study aimed to validate a previously developed scoring system on a larger cohort size. Methods: Patients admitted to an intensive cardiovascular care unit were divided into three groups: (a) patients diagnosed with TS, (b) females with anterior MI, and (c) other all-comer STEMIs. A 10-point scoring system was used: stressful events (three points), female gender (two points), no history of diabetes mellitus (two points), estimated left ventricular ejection fraction (LVEF) ≤ 40% on admission echocardiography (one point), positive troponin on admission (one point), and no smoking (one point). A t-test was applied to the three study groups, sensitivity and specificity testing was performed using the ROC curve method. Results: A total of 1150 patients were included in our study: 54 with TS, 97 females with anterior MI and 999 other all-comer STEMIs. Patients in the TS group were predominantly females with a higher rate of stressful events prior to admission, lower rates of diabetes mellitus and smoking, and lower LVEF% systolic function compared to the STEMI cohort. In a multivariate logistic regression analysis, the average TS scoring system was significantly higher in the TS group compared with the anterior STEMI and all-comer STEMI groups (8.3 vs. 5.7 vs. 3.83, p < 0.001, respectively) with an AUC of 0.83 for TS score ≥ 8. Conclusions: The 10-point TS scoring system is an easy, reliable, and useful diagnostic tool that might help in distinguishing patients with TS and ACS.